Oriented Thiophene-Extended Benzotrithiophene Covalent Organic Framework Thin Films: Directional Electrical Conductivity - Frey, Laura; Poehls, Jonas Fredrik; Hennemann, Matthias; Maehringer, Andre; Reuter, Stephan; Clark, Timothy; Weitz, Ralf Thomas; Medina, Dana Dina (Advanced Functional Materials, 2022)
The synthesis of covalent organic frameworks (COFs) based on a novel thiophene-extended benzotrithiophene (BTT) building block is described, which in combination with triazine-based amines (1,3,5-triazine-2,4,6-triyl)trianiline (TTA) or (1,3,5-triazine-2,4,6-triyl)tris(([1,1´-biphenyl]-4-amine)) (TTTBA)) affords crystalline, and porous imine-linked COFs, BTT TTA and BTT TTTBA, with surface areas as high as 932 and 1200 m2 g−1, respectively. Oriented thin films are grown successfully on different substrates, as indicated by grazing incidence diffraction (GID). Room-temperature in-plane electrical conductivity of up to 10−4 S m−1 is measured for both COFs. Temperature-dependent electrical conductivity measurements indicate activation energies of ≈123.3 meV for BTT TTA and ≈137.5 meV for BTT TTTBA and trap-dominated charge transport via a hopping mechanism for both COFs. Moreover, conductive atomic force microscopy reveals directional and defect-dominated charge transport in the oriented BTT COF films with a strong preference for the in-plane direction within the molecular 2D-planes. Quantum mechanical calculations predict BTT TTTBA to conduct holes and electrons effectively in both in-plane and out-of-plane directions. In-plane, charge carrier transport is of hopping character where the triazine cores represent the barrier. Out-of-plane, a continuous charge-carrier pathway is calculated that is hampered by an imposed structural defect simulated by a rotated molecular COF layer.
CRIS-Team Scopus Importer:2022-09-09
Keywords: benzotrithiophene; covalent organic frameworks; electrical conductivity; thin films